Spremljava likovnega razvoja učencev v tretjem vzgojno-izobraževalnem obdobju osnovne šole: analiza stanja z vidika spola - Herzog, Jerneja (Revija za elementarno izobraževanje, 2017)
Monitoring the Artistic Development of Students in the Third Education Cycle of Primary School – Analysis of the Current Situation from a Gender Perspective. Modern trends in education tend toward promoting autonomy, the creation of an integrated personality, and—last but not least—creativity. From this perspective, the question emerges to what extent our education system supports the development of a child’s personality, and to what extent attention is genuinely paid to the development of creativity, in practice. The article presents the results of a study that monitored the level of artistic creativity and the level of artistic formative ability among seventh-grade students in Slovenian primary schools. At the age of the second education cycle, boys and girls develop differently; consequently, in the selection of art-educational procedures and methods different approaches must be adopted, and as a result, the emphasis in this study was on the examination of differences between the genders.